2004
DOI: 10.1111/j.1468-5906.2004.00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Specifying the Impact of Conservative Protestantism on Educational Attainment

Abstract: Recent studies have demonstrated that conservative Protestantism negatively affects educational advancement. However, these studies have treated conservative Protestantism as a monolithic religious bloc that uniformly constrains achieving higher education. Disaggregating conservative Protestantism into fundamentalists, Pentecostals, and evangelicals reveals that the relationship between conservative Protestantism and educational attainment is more complex than recently shown. Findings from a nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(127 citation statements)
references
References 40 publications
5
119
0
Order By: Relevance
“…Prior work has shown that different secular outcomes for religious individuals are often especially salient among the highly religious who adhere to strict, high-tension faiths (cf. Grasmick, Kinsey, and Cochran, 1991;Hammond, Cole, and Beck;1993;Beyerlein, 2004;Berman, 2000;Cochran and Beeghley, 1991); this focus of the model on the highly religious is thus reasonable.…”
Section: Proposition: Suppose There Are Two Types Of Individuals Higmentioning
confidence: 99%
“…Prior work has shown that different secular outcomes for religious individuals are often especially salient among the highly religious who adhere to strict, high-tension faiths (cf. Grasmick, Kinsey, and Cochran, 1991;Hammond, Cole, and Beck;1993;Beyerlein, 2004;Berman, 2000;Cochran and Beeghley, 1991); this focus of the model on the highly religious is thus reasonable.…”
Section: Proposition: Suppose There Are Two Types Of Individuals Higmentioning
confidence: 99%
“…The same was true in the black sample. Recent research highlights the importance of considering more refined distinctions within the conservative Protestant group(Beyerlein, 2004); unfortunately this was not possible given the information available in the 1995 NSFG.Religion and high-school graduation 283…”
mentioning
confidence: 99%
“…1 Emphasizing the Economics literature, and to a lesser extent the Sociology literature, religiosity and religious affiliation have been related, among other things, to education (Freeman, 1986;Claudia Goldin and Lawrence Katz, 1999;Lehrer, 2004;Kraig Beyerlein, 2004), employment and work hours (Richard Freeman, 1986) wages, income and wealth accumulation (Claudia Goldin and Lawrence Katz, 2000;Lisa Keister, 2003;Evelyn Lehrer, 2004a,b); mate choice, cohabitation, marital stability, fertility and female labor force participation (Thornton et al 2007;Lehrer, 2004a;Charles Manski and Joram Mayshar, 2002); intergenerational transfers (Scott Myers, 2004), tobacco use (Frank Chaloupka, Michael Grossman and John Tauras, 1997;Tauras and Chaloupka, 1999), alcohol use (Rosalie Pacula, 1998), substance abuse and other types of social deviance (Freeman, 1986;Pacula et al, 2000;Richard Gorsuch, 1995), suicide (Emile Durkheim, 1897), child abuse (Sara Markowitz and Grossman, 1996), physical and mental health (David Williams, et al 1991;Valerie Dull and Laurie Skokan, 1995;W. Larry Ventis, 1995;Christopher Ellison, 1998; Jeffrey , subjective well-being (David Blanchflower and Andrew Oswald, 1997; Jeffrey , organ donation (Naci Mocan and Erdal Tekin, 2005), work ethic 1 Given the limitations of our data, we will not be able to separate differences in religious preferences from differences in religious beliefs, so we will not emphasize this distinction and treat religious differences as a matter of preferences.…”
Section: Introductionmentioning
confidence: 99%